Stereoselective synthesis of a 4-⍺-glucoside of valienamine and its X-ray structure in complex with Streptomyces coelicolor GlgE1-V279S - Anshupriya Si (Nature Portfolio, 2021)
Abstract Glycoside hydrolases (GH) are a large family of hydrolytic enzymes found in all domains of life. As such, they control a plethora of normal and pathogenic biological functions. Thus, understanding selective inhibition of GH enzymes at the atomic level can lead to the identification of new classes of therapeutics. In these studies, we identified a 4-⍺-glucoside of valienamine (8) as an inhibitor of Streptomyces coelicolor (Sco) GlgE1-V279S which belongs to the GH13 Carbohydrate Active EnZyme family. The results obtained from the dose–response experiments show that 8 at a concentration of 1000 µM reduced the enzyme activity of Sco GlgE1-V279S by 65%. The synthetic route to 8 and a closely related 4-⍺-glucoside of validamine (7) was achieved starting from readily available D-maltose. A key step in the synthesis was a chelation-controlled addition of vinylmagnesium bromide to a maltose-derived enone intermediate. X-ray structures of both 7 and 8 in complex with Sco GlgE1-V279S were solved to resolutions of 1.75 and 1.83 Å, respectively. Structural analysis revealed the valienamine derivative 8 binds the enzyme in an E2 conformation for the cyclohexene fragment. Also, the cyclohexene fragment shows a new hydrogen-bonding contact from the pseudo-diaxial C(3)–OH to the catalytic nucleophile Asp 394 at the enzyme active site. Asp 394, in fact, forms a bidentate interaction with both the C(3)–OH and C(7)-OH of the inhibitor. In contrast, compound 7 disrupts the catalytic sidechain interaction network of Sco GlgE1-V279S via steric interactions resulting in a conformation change in Asp 394. These findings will have implications for the design other aminocarbasugar-based GH13-inhibitors and will be useful for identifying more potent and selective inhibitors.